Evaluación de disfunción autonómica en pacientes con insuficiencia renal crónica en programa de hemodiálisis. - CONTRERAS RIOS, Rafael; HURTADO ARESTEGUI, Abdías (Revista Médica Herediana, 2013)
Objective: To determine the frequency of autonomic dysfunction and associated factors in patients with chronic renal failure in hemodialysis program. Material and methods: A case-control study we evaluated 30 patients in hemodialysis program and equal number of healthy volunters, using the heart rate variability test during deep breathing. Results: In hemodialysis group, twenty two patients (80%) had autonomic dysfunction, 67% were asimptomatics. In control group only two patients had autonomic dysfunction (6.7%). In both groups, we found positive correlation than age with autonomic dysfunction stage. Conclusion: Autonomic dysfunction is a frequent complication in hemodialysis patients; it’s frequently asymptomatic and it has age relationship.